Bone sarcoma follow-up; a nationwide analysis of oncological events after initial treatment - Louren M. Goedhart; Vincent K.Y. Ho; Joris J.W. Ploegmakers; Ingrid C.M. van der Geest; Michiel A.J. van de Sande; Jos A. Bramer; Martin Stevens; Paul C. Jutte (Journal of Bone Oncology, 2023)
Aim: Follow-up strategies for high-grade bone sarcomas have been optimized to facilitate early detection of local recurrence and distant metastasis. The ideology is that early detection enables early treatment presuming better survival. However, the clinical value for each individual patient remains questionable. This study aims to evaluate oncological events after initial treatment in order to assess current follow-up strategies for high-grade bone sarcomas in the Netherlands. Patients and Methods: A retrospective cohort study was conducted based on a national registry. All cases were retrieved from the Netherlands Cancer Registry. Our study consisted of 393 patients treated between 2007 and 2011 with complete follow-up data. Baseline characteristics were analysed for all entities. Local recurrence and distant metastasis was analysed along with overall survival for high-grade chondrosarcoma, high-grade osteosarcoma, Ewing sarcoma and chordoma. Results: Median follow-up was 8,3 years for high-grade chondrosarcoma, 4,9 for high-grade osteosarcoma, 3,8 for Ewing sarcoma and 7,5 for chordoma. Median time to local recurrence and distant metastasis was 1,2 years for high-grade osteosarcoma and 1,5 years for Ewing sarcoma. For high-grade osteosarcoma with localized disease at presentation, 0.09 new distant metastatic events per patient per year were seen after five years of follow-up with 11,1 patients needed to follow-up for any event. Five-year overall survival was 60,0% for high-grade chondrosarcoma, 50,0% for high-grade osteosarcoma, 45,3% for Ewing sarcoma and 71,4% for chordoma. Conclusions: This nationwide study shows a plateau in local recurrences and distant metastatic events after four years of treatment for patients with high-grade osteosarcoma and Ewing sarcoma. Due to a lack of reliable evidence however, we were not able to provide additional guidance on follow-up intervals and duration. Collaborative research with larger groups is needed in order to provide a solid scientific recommendation for follow-up in the heterogenous patient population with bone sarcoma.